1984
DOI: 10.1007/bf00511059
|View full text |Cite
|
Sign up to set email alerts
|

Human skin grafts on nude athymic mice: A light microscopic stereological study

Abstract: A morphometric procedure is presented, which allows quantitative information to be obtained from the epidermis at the light microscope level. The application of this procedure to human skin grafted to the nude mouse revealed acanthosis of the grafted epidermis compared to the original donor skin. All epidermal layers were thicker, but the increase in the granular layer was especially marked. The ratio of the basement membrane surface to the epithelial surface showed no significant change. A possible explanatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
1
1
1
Order By: Relevance
“…Hence, in the present study, despite the observed hyperproliferation and increase in pigmentation of the graft which had also been reported by other authors [25], we found no change in the structure and composition of epidermal lipids.…”
Section: Discussioncontrasting
confidence: 51%
“…Hence, in the present study, despite the observed hyperproliferation and increase in pigmentation of the graft which had also been reported by other authors [25], we found no change in the structure and composition of epidermal lipids.…”
Section: Discussioncontrasting
confidence: 51%
“…3) with the exception of a slight de crease of the graft size and an increase of the epidermal thickness. The last observation has recently been verified by quantitative mor phometric analyses in human skin grafts on nude mice [3]. The results were, therefore, nearly identical to those, obtained in the nude mouse.…”
supporting
confidence: 70%
“…Another feature that is easily estimated by stereological techniques is mean epidermal thickness. Human skin grafted onto nude mice was shown to exhibit acanthosis over time following transplantation and the magnitude of acanthosis and the degree to which each separate epidermal layer contributed to this was determined using line intercepts and point counting (37). The pilosebaceous unit was studied in patients with senile sebaceous gland hyperplasia and both the relative volume (with regards to the dermal volume) of the pilosebaceous unit, the sebaceous gland and differentiated sebaceous epithelium were found to have a higher relative volume compared with healthy controls using simple point counting and light microscopy on haematoxylin-eosin stained sections (38).…”
Section: Applied Stereologymentioning
confidence: 99%